2020
DOI: 10.1038/s41531-020-00130-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of asleep and awake deep brain stimulation robot-assisted surgery for Parkinson’s disease

Abstract: To compare the differences between asleep and awake robot-assisted deep brain stimulation (DBS) surgery for Parkinson’s Disease (PD), we conducted this retrospective cohort study included 153 PD patients undergoing bilateral robot-assisted DBS from June 2017 to August 2019, of which 58 cases were performed under general anesthesia (GA) and 95 cases under local anesthesia (LA). Procedure duration, stimulation parameters, electrode implantation accuracy, intracranial air, intraoperative electrophysiological sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
20
2
Order By: Relevance
“…21,23,24 To date, pneumocephalus has not been correlated with increased operative time, postoperative complications, or increased postoperative Unified Parkinson Disease Rating Scale measurements. [25][26][27] In our current study, pneumocephalus was only slightly correlated with older age and not associated with radial error and number of MER passes per cases, nor procedure time. Age-related cortical atrophy creating a larger space for air to enter could explain the associated increased pneumocephalus.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…21,23,24 To date, pneumocephalus has not been correlated with increased operative time, postoperative complications, or increased postoperative Unified Parkinson Disease Rating Scale measurements. [25][26][27] In our current study, pneumocephalus was only slightly correlated with older age and not associated with radial error and number of MER passes per cases, nor procedure time. Age-related cortical atrophy creating a larger space for air to enter could explain the associated increased pneumocephalus.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, variable pneumocephalus volumes have been reported, as shown in select studies undergoing awake DBS (Table 4). 22,23,25,26,28,29 Mean pneumocephalus volumes spanned from 2.1 to 20.8 cm 3 in these studies, with our study's mean volume of 12.8 cm 3 within the middle of this range. In the 8 patients of our study presenting with volumes between 20 and 30 cm 3 , the number of MER passes and radial error was not increased relative to the remaining cohort.…”
Section: Discussionsupporting
confidence: 55%
“…Our study found no significant differences in the incidence of intracerebral hemorrhages or infections between the LA and GA group. However, the awake group had a larger intracranial air volume ( Blasberg et al, 2018 ; Ko et al, 2018 ; Jin et al, 2020 ). There are two possible explanations.…”
Section: Discussionmentioning
confidence: 89%
“…Understanding the position of the electrode relative to the neuroanatomy could potentially facilitate both targeting and programming [8]. The value of imaging is highlighted by the significant increase in reports of equally efficacious outcomes with image-guided "asleep" implantation [9][10][11]. Patient-specific imaging data can also be paired with three-dimensional stimulation field models (SFMs) representing the volume of tissue activated (VTA) [12].…”
Section: Introductionmentioning
confidence: 99%